Efficient in vitro regeneration and genetic fidelity analysis of shea tree (Vitellaria paradoxa Gaertn) using ISSR markers - Affi Jean Paul Attikora; Souleymane Silué; Mongomaké Kone; Napkalo Silue; Yves Kwibuka; Saraka Didier Martial Yao; Caroline De Clerck; Sok Lay Him; Nafan Diarrassouba; Taofic Alabi; Ludivine Lassois (Electronic Journal of Biotechnology)
Background: Shea tree is an economically valuable tree crop in the food, cosmetic, and pharmaceutical industries due to its seed oil, known as shea butter. Rapid propagation of superior shea trees through in vitro culture is essential to support domestication and conservation efforts. This study aimed to establish an efficient in vitro propagation protocol for the regeneration of shea true-to-type plantlets. Nodal explants were cultured on half-strength Murashige and Skoog (MS) medium supplemented with 6-benzylaminopurine (BAP) and/or kinetin (Kin) combined with 1-naphthaleneacetic acid (NAA) for shoot induction. Rooting was tested on half- and quarter-strength MS and full- and half-strength modified MS (MS1B) media, enriched with indole-3-butyric acid (IBA) alone or combined with NAA, IAA, meta-topolin (mT), and putrescine. Genetic fidelity of regenerated plants was assessed using inter-simple sequence repeat (ISSR) markers. Results: The results showed that MS/2 medium containing 3:1.2:1 mg/L BAP:Kin:NAA gave the best regeneration of axillary shoots. Four-week-old axillary shoots were 100% rooted on MS1B/2 medium containing 3:0.1:40 mg/mL IBA:mT:putrescine. Rooted plantlets were successfully acclimated in vivo. The polymorphism of the ISSR markers ranged from 50 to 87.5%, with an average of 65%, and the polymorphism information content was 0.22. For genetic fidelity assessment, 34 scorable and reproducible markers were obtained. All markers were monomorphic and identical to the mother plant. Conclusions: The micropropagation protocol proposed in this study is suitable for large-scale in vitro regeneration of shea without genetic alteration. However, further studies are needed for the induction of multiple micros-hoots.How to cite: Attikora AJP, Silué S, Kone M, et al. Efficient in vitro regeneration and genetic fidelity analysis of shea tree (Vitellaria paradoxa Gaertn) using ISSR markers. Electron J Biotechnol 2025;75. https://doi.org/10.1016/j.ejbt.2025.01.007.